Delightful Artistry: Peningkatan Kompetensi Siswa SMKN 2 Singaraja melalui Pelatihan dibidang Pastry & Dessert Plating - Ni Made Sri Rahayu; Ni Luh Supartini; Putu Sri Darmayanti (Journal of Conflict and Social Class (JCSC), 2025)
SMKN 2 Singaraja is a vocational high school in Bali focused on developing student competencies, including in the culinary field. To enhance human resource quality and align graduates with industry needs, the school collaborated with IPB International through a Community Service (PKM) program offering training in pastry and dessert plating. This training aimed to improve students' practical skills in baking and aesthetically presenting desserts. The methods employed included discussion, question-and-answer sessions, recipe-based modules, hands-on practice, and pre- and post-training evaluations. Evaluation results showed that 65% of participants were able to produce pastries according to the taught recipes, while 90% expressed satisfaction with their final products. All participants highly rated the instructors’ expertise, practical facilities, materials, and event organization. The training enhanced not only technical skills in pastry making but also soft skills such as creativity and teamwork. This initiative is expected to serve as a sustainable model for vocational competency development and encourage student entrepreneurship in the culinary sector. The collaboration between vocational schools and higher education institutions proves effective in strengthening the quality of vocational education in Indonesia.